The Disoeuvre: an Argument in 4 Voices (WASL Table); version 4:27. (2nd October 2018) - Allen, Felicity
Abstract : The Disoeuvre: an Argument in 4 Voices (WASL Table ) ; version 4:27 contributes to Felicity Allen's long-term project, The Disoeuvre . Allen first invented, named and explored the concept of The Disoeuvre in her PhD, "Creating the Disoeuvre: Interpreting Feminist Interventions as an Expanded Artistic Practice in Negotiation with Art's Institutions". The four voices of The Disoeuvre: an Argument in 4 Voices (WASL Table ) ; version 4:27 work across and down each page in four strands: (1) photograph, (2) diaristic/album note, (3) didactic argument shifting through multiple pronoun positions from pronounced objectivity to pronounced subjectivity, and (4) quotations from texts read by the artist who has given herself permission to make no more than 27 variations of this work. In 1978, Allen was a founder member of the Women Artists Slide Library (WASL) in London, and decades later her Middlesex University supervisors suggested that her WASL work might be presented in her PhD (completed in 2016). However, she and the other early founders of the library had preserved hardly any documentation of their activism. The table on which she continues to work, originally passed on to her for WASL in 1978 but too big for WASL's first public office in 1982, is perhaps an equivalent to documentation; staying with her throughout her career, the table also suggests undercurrents in her own Disoeuvre.